Long-term Practice with Domain-Specific Task Constraints Influences Perceptual Skills - Oppici, Luca; Panchuk, Derek; Serpiello, Fabio R.; Farrow, Damian (Frontiers in Psychology, 2017)
The long-term impact of practice with different task constraints on perceptual skill is relatively un-explored. This study examined the influence of extensive practice, i.e., more than a thousand hours of structured practice, with domain-specific task constraints on perceptual skill associated with the passing action. Despite performing the same passing skill, it is not known whether long-term exposure to specific soccer or futsal task constraints influences the players’ attunement to environmental information. This study examined this issue by assessing the attention orientation of soccer (n=24) and futsal players (n=24) during modified games (6 v 6). Futsal players had higher scanning behavior during ball reception and control (40% more ball-player attention alternations) while soccer players mainly scanned the environment when not in ball possession (25% more attention alternations). We suggest that the behavioral differences found are elicited by the extensive domain-specific practice. That is, the higher number of players in soccer, and by a more intense game and easier to control ball in futsal. This study provides new insights into the long-term effects of practicing with specific task constraints.